(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
One of the world’s most rapidly expanding sectors right now is computer software. Effectivestrategies for predicting software costs are clearly needed to reduce expenses and make software morecompetitive in light of the rising price of software development. Software cost assessment has made useof a variety of computational methodologies. As a result, it may be difficult for software managers toallocate resources or keep expenses under control if estimates of development time and cost varywidely. Predicting the amount of time and effort it will take to implement a software system is the primarygoal of software cost estimate. It’s a crucial job that aids the software industry in properly managing thesoftware development process they’re involved in.